2018
DOI: 10.1016/j.compositesa.2018.01.023
|View full text |Cite
|
Sign up to set email alerts
|

The effect interleaving has on thin-ply non-crimp fabric laminate impact response: X-ray tomography investigation

Abstract: To improve the damage resistance and tolerance of thin laminates manufactured with thin-ply non-crimp-fabrics, we interleaved non-woven veils (two different types of co-polyamide veil were studied) into the interlaminar regions. We devised an impact, compression after impact (CAI) and quasi-static indentation experimental campaign, where X-ray micro-computed tomography illustrated how: (a) matrix cracking, delamination and fibre failure interact during out-of-plane loading and (b) interleaving affects the thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…During infusion, resin flows more rapidly through the highly permeable veils than through the reinforcement fabrics and accrues in interlaminar regions, creating resin-rich interlaminar regions and increasing inter-ply thickness. 2,8 Moreover, local variations in preform permeability induce distorted flow fronts, resulting in air entrapment and dry spot formation, particularly within fiber tows. 13,[50][51][52] The formed intra-tow voids tend to migrate to resin-rich regions such as veil interfaces, as formation of voids in resin-rich areas is energetically more favorable than formation of voids within fiber bundles.…”
Section: Cure Cycle Modification and Part Manufacturementioning
confidence: 99%
See 4 more Smart Citations
“…During infusion, resin flows more rapidly through the highly permeable veils than through the reinforcement fabrics and accrues in interlaminar regions, creating resin-rich interlaminar regions and increasing inter-ply thickness. 2,8 Moreover, local variations in preform permeability induce distorted flow fronts, resulting in air entrapment and dry spot formation, particularly within fiber tows. 13,[50][51][52] The formed intra-tow voids tend to migrate to resin-rich regions such as veil interfaces, as formation of voids in resin-rich areas is energetically more favorable than formation of voids within fiber bundles.…”
Section: Cure Cycle Modification and Part Manufacturementioning
confidence: 99%
“…Previous studies have demonstrated that insertion of non-woven thermoplastic veils increases impact strength of thermoset composites, [1][2][3][4][5][6][7] yet can also cause increased porosity because of local variations in preform permeability created by the highly permeable veils. 2,8 One of these reports speculated that modifying the manufacturing process to provide more time for resin to saturate dry regions may reduce laminate void content, 2 although no such studies have been reported. To promote impregnation of partially saturated interlaminar regions, a lowtemperature post-infusion dwell was introduced to allow greater time for low-viscosity resin to equilibrate pressure and redistribute during the post-filling stage.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations